Effectiveness of vitamin D3 supplementation with protein realimentation in osteoblast and osteoclast of the maxilla of breastfed malnourished rat infants - Hidayah, Riski Amalia; Kurniawan, Aris Aji; Widyaningsih, Pratiwi Nur; Rakhmawati, Rakhmawati (Majalah Kedokteran Gigi Indonesia, 2023)
Child malnutrition can happen because of lack of nutrition during pregnancy. Malnutrition can cause low birth weight in babies. This can cause jaw and alveolar bone abnormalities that can lead to malocclusion, periodontitis, and others. This condition can affect bone cells, such as osteoblast and osteoclast. Vitamin D3 supplementation accompanied by protein realimentation may promote optimum bone growth. This research aims to investigate the effect of protein realimentation and vitamin D3 on osteoblast and osteoclast of malnourished rat pups’ maxilla. In this research, the rat pups were divided into 5 groups: a positive control group (K+), a negative control group (K-), and 3 treatment groups (P1, P2, and P3). The subjects of this research were 10 male and 30 female Wistar rats. A condition of malnutrition was induced in the rat pups and they were given vitamin D3 supplementation with protein realimentation. Rat pups in each group were euthanized on the 22nd day to observe the number of osteoclast and osteoblast in the maxilla. The results showed that the number of osteoblasts between normal and malnourished rats was significantly different (p value < 0.05), but the number of osteoclasts between rats in the control and treatment groups was not significantly different. Administration of vitamin D3 may affect the number of osteoblasts and may not affect the number of osteoclasts on bone. The effective dose of vitamin D3 is 0.36 IU/day.